Conceptualizing peri-urban-rural landscape change for sustainable management - Mrinalini Goswami (Bangalore, 2018)
Urbanization has been a spontaneous phenomenon resulting from economic activities for the well-being of society, with consequent adverse impacts. In 2010, more than half of the global population lived in cities, and urban population will be 70% by 2050. (WHO, 2010).In countries like India, the alteration of villages into urban centre is very rapid, transforming demographic, economic and biophysical characteristics of the landscape. In this process of transformation, eco-sensitive areas and rural population dependent on natural resources are threatened in many ways, including their livelihoods, socio-ecological and cultural settings. The transitional peri-urban areas have been recognized in spatial and economic terms in Indian context with regard to commodity flow, housing, peri-urban agriculture and pollution in recent years. An integrated approach to identify the peri-urban concerns and evolve a landscape level management strategy is still missing. This paper examines the existing research in this area to look into an effective and viable approach for the assessment of peri-urban landscape change to develop a sustainable landscape management strategy.
Keywords: Sustainable landscape management; Urbanization